Synthesis and study of isoindolo[2,1-a]benzimidazoles in the cycloaddition reactions: UDC 547.759.4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
Reaction of isoindolo[2,1-a]benzimidazoles with maleimides was studied. Obtained adducts were studied with NMR 1H, 13C, and COSY spectroscopy techniques, X-Ray.
Keywords: -